PERKEMBANGAN DAN TANTANGAN PERS WANITA DALAM INDUSTRI PERS - Kusumastuti, Frida (Jurnal Bestari, 1994)
In general, press has four functions, namely education, information, social control, and entertainment. In Indonesia knowing the history of women's press is rather difficult because we are lack of the data. In early of 20 th century there were some women megazines namely, poetri Hindia, soenting Melayu, doenia isteri, poetri merdeka etc. Those women megazines, however, seem that they not given much meaningfulness to the women yet.